2014
DOI: 10.1159/000363410
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Extract Inhibition of Human Leiomyoma Cell Proliferation Is Mediated via Catechol-<b><i>O</i></b>-Methyltransferase

Abstract: Background/Aims: To investigate the inhibitory effect of green tea extract, epigallocatechin gallate (EGCG), on wild-type human leiomyoma (WT-HuLM) cells and its potential action via catechol-o-methyltransferase (COMT) activity. Methods: Cell proliferation of WT-HuLM and COMT gene-silenced HuLM (COMT-shRNA-HuLM) cells treated with 0 or 100 µM EGCG for 7 days was measured using the MTT method. Total RNA and protein were extracted from cells treated with 0 or 100 µM of EGCG for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 66 publications
0
22
0
1
Order By: Relevance
“…The average daily intake of EGCG from green tea consumption in the EU ranges from 90 to 300 mg/day, while high-level consumers intake even up to 860 mg EGCG/day. In vitro studies showed that EGCG, consumed in the form of a green tea extract, inhibited proliferation and growth and promoted apoptosis in cultures of human uterine leiomyoma cells in a dose-dependent manner [94,95]. Antiproliferative and gene-modulating effects of EGCG were partially mediated through the effect on catechol-O-methyltransferase (COMT) enzyme activity.…”
Section: Green Tea-polyphenolsmentioning
confidence: 99%
“…The average daily intake of EGCG from green tea consumption in the EU ranges from 90 to 300 mg/day, while high-level consumers intake even up to 860 mg EGCG/day. In vitro studies showed that EGCG, consumed in the form of a green tea extract, inhibited proliferation and growth and promoted apoptosis in cultures of human uterine leiomyoma cells in a dose-dependent manner [94,95]. Antiproliferative and gene-modulating effects of EGCG were partially mediated through the effect on catechol-O-methyltransferase (COMT) enzyme activity.…”
Section: Green Tea-polyphenolsmentioning
confidence: 99%
“…D (whose influence on COMT has been reported [123]), vit. D supplementation, consumption of large quantities of green tea, or supplementation of its extracts [124].…”
Section: Available Immunohistochemical Markersmentioning
confidence: 99%
“…These data support our hypothesis, and suggest that UtLM‐ht cells express active COMT, and that COMT is involved in regulating the sensitivity of cells to EGCG‐based therapy. Zhang et al [] also demonstrated the presence of active COMT in a human uterine leiomyoma cell line; however, their conclusions are obfuscated by their use of non‐physiological concentrations of EGCG (100 μM). Consistent with the study reported here, we have previously shown that DNC treatment increases the biological activity of EGCG and Pro‐EGCG in human breast cancer MDA‐MB‐231 cells—a cell line with a high level of COMT activity [Huo et al, ; Landis‐Piwowar et al, ].…”
Section: Resultsmentioning
confidence: 99%